(untitled) - Gass, Susan M; Behney, Jennifer (New York, 2013)
Includes bibliographical references and indexes.; This work is a revised edition of the text first published in 1994. The authors retain the multidisciplinary approach that presents research from linguistics, sociology, psychology, and education, in a format designed for use in an introductory course for undergraduate of graduate students. New chapters have been added, which cover: child language acquisition; universal grammar; and instructed language learning. New sections address that data analysis does not show, replication of research findings, interlanguage transfer, the aspect hypothesis, general nativism, connectionist approaches, and implicit/explicit knowledge
Keywords: Second language acquisition